The state of data analytics and visualization adoption - Sarrel, Matthew D. (O'Reilly Media, 2017)
Businesses regardless of industry or company size increasingly rely on data analytics and visualization to gain competitive advantage. That's why organizations today are racing to gather, store, and analyze data from many sources in a wide range of formats. In the spring of 2017, Zoomdata commissioned an O'Reilly survey to assess the state of data analytics and visualization technology adoption across several industries, including manufacturing, financial services, and healthcare. Roughly 875 respondents answered questions online about their industry, job role, company size, and reasons for using analytics, as well as technologies they use in analytics programs, the perceived value of analytics programs, and many other topics. This report reveals: The industries furthest along in adopting big data analytics and visualization technologies The most commonly analyzed sources of big data The most commonly used technologies for analyzing streaming data Which analytics skills are in most demand The most valued characteristic of big data across all industries The types of users big data analytics and visualization projects typically target If you're a technology decision maker, a product manager looking to embed analytics, a business user relying on analytics, or a developer pursuing the most marketable skills, this report provides valuable details on today's data analytics trends.